Pengaruh Perubahan Tegangan Tabung (kVp) Terhadap CT Number dan Uniformitasnya pada Pesawat CT Scan - S., Anugrah Ariyani; Setiabudi, Wahyu; Anam, Choirul (JURNAL SAINS DAN MATEMATIKA, 2012)
An examination of consistency of CT numbers and its uniformity due to variation of the tube voltage has been done. The examination was conducted using water and polyethyelene phantoms as a test object. The method of scanning, which are axial scanning and helical scanning. The scanning was taken 5 (five) slices with slice thickness of 5 mm. Variations in tube voltage used were 80 kV, 120 kV and 140 kV. The tube current 160 mA and time scanning 2 seconds. It was obtained that the increase in voltage from 80 kV to 140 kV led to increase the value of CT number both for water and polyethylene phantoms. The uniformity of CT number for all ROI varies, but still within the range of tolerance limits. The CT number for the water phantom does not exceed 0 ± 5 HU and for polyethylene phantom does not exceed -300 to -100 HU.. Keywords: CT Scan, CT number, uniformity, tube voltage (kV)